2017
DOI: 10.21577/0100-4042.20170136
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Cyclohexanol on Phosphotungstic Acid Anion Intercalated Layered Double Hydroxides With Aqueous H2o2 as Oxidant

Abstract: The layered double hydroxides (LDH) of Mg 2 AlNi and Mg 3 Al pillared by Keggin-type phosphotungstic acid anion (POM), i.e. Mg 2 AlNi-POM LDH and Mg 3 Al-POM LDH were synthesized by an ion-exchange method. The synthesized POM intercalated LDH compounds were characterized using various techniques such as FTIR, XRD, TGA and BET. The observed results show that the obtained catalysts retain the layer structure of LDH. Compared with the binary Mg 3 Al-POM LDH, the ternary Mg 2 AlNi-POM LDH catalyst indicated a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It is noteworthy that the position of the (003) diffraction peak moves from the original 10.79° of CoNi-LDH to a lower 2θ diffraction angle of 6.06°. According to Bragg’s equation (2 d sin θ = n λ, where d represents the layer spacing, n = 1, λ = 0.15406 nm), , the layer spacings of pristine NO 3 – intercalated CoNi-LDH and P 8 W 48 /CoNi-LDH can be calculated as 0.82 and 1.46 nm, respectively. The gallery height value of 0.98 nm can be obtained by subtracting the thickness of the host layer (0.48 nm) from the d -spacing value of P 8 W 48 /CoNi-LDH, which is almost equivalent to the theoretical diameter of the short axis of P 8 W 48 determined from the crystallographic data (1.0 nm) .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that the position of the (003) diffraction peak moves from the original 10.79° of CoNi-LDH to a lower 2θ diffraction angle of 6.06°. According to Bragg’s equation (2 d sin θ = n λ, where d represents the layer spacing, n = 1, λ = 0.15406 nm), , the layer spacings of pristine NO 3 – intercalated CoNi-LDH and P 8 W 48 /CoNi-LDH can be calculated as 0.82 and 1.46 nm, respectively. The gallery height value of 0.98 nm can be obtained by subtracting the thickness of the host layer (0.48 nm) from the d -spacing value of P 8 W 48 /CoNi-LDH, which is almost equivalent to the theoretical diameter of the short axis of P 8 W 48 determined from the crystallographic data (1.0 nm) .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The lattice fringes with the interplanar distance of 2.56 Å corresponds to the (012) facet of P 8 W 48 /CoNi-LDH can be observed in the high-resolution (HR) TEM image (Figure 1g). 52 The scanning transmission electron microscopy (STEM) mapping results exhibited in Figure 1h 47,53 the layer spacings of pristine NO 3 − intercalated CoNi-LDH and P 8 W 48 /CoNi-LDH can be calculated as 0.82 and 1.46 nm, respectively. The gallery height value of 0.98 nm can be obtained by subtracting the thickness of the host layer (0.48 nm) from the d-spacing value of P 8 W 48 /CoNi-LDH, which is almost equivalent to the theoretical diameter of the short axis of P 8 W 48 determined from the crystallographic data (1.0 nm).…”
Section: Synthesis and Characterization Of P 8 W 48 /Coni-ldhmentioning
confidence: 99%
“…The interlayer anions could be replaced with HPA anions through calcination of HT and impregnation method [15]. Activity of HPA-HT was reported for various chemical reaction for example oximation process where aldehydes and ketones react with hydroxylamine [16], oxidation of cyclohexane [17] and aerobic oxidation [10]. Previous studies also reported that HPA-HT possess better recovery, large surface area and thermalstability in catalytic process [18] [19].…”
Section: Introductionmentioning
confidence: 99%